2018
DOI: 10.1111/jphs.12244
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease: cost-driving factors and impact of cost sharing on outpatient resource utilization

Abstract: Objectives (1) To identify the cost‐driving factors of health expenditure in inflammatory bowel disease (IBD), (2) to determine the effect of different cost‐sharing levels on outpatient visits and (3) to determine the effect of different cost‐sharing levels on medication adherence among patients with IBD. Method This was a retrospective, longitudinal study in which data were collected from 1999 to 2013 using the Medical Expenditure Panel Survey. The study sample included all patients who had IBD, were at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…The remaining 4837 studies were screened on title and abstract and 4730 excluded. After full‐text screening, 64 of the remaining 107 studies were included in the systematic review 32‐95 . No missed studies were found in the reference lists of the other systematic reviews.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 4837 studies were screened on title and abstract and 4730 excluded. After full‐text screening, 64 of the remaining 107 studies were included in the systematic review 32‐95 . No missed studies were found in the reference lists of the other systematic reviews.…”
Section: Resultsmentioning
confidence: 99%
“…After full‐text screening, 64 of the remaining 107 studies were included in the systematic review. 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ,…”
Section: Resultsmentioning
confidence: 99%